Asas Persetujuan Dalam Perkawinan Menurut Hukum Islam: Menelaah Penyebab Terjadinya Kawin Paksa - Hasibuan, Zulfan Ependi (IAIN Padangsidimpuan, 2019)
A perfect marriage is a marriage that meets the terms and conditions, and upholds the principles of marriage. A perfect marriage will be realized in a sakinah, mawaddah and rahmah family. However, the phenomenon of forced marriages is considered to be able to reduce the harmony in marriage and even destroy the values of the principle of marriage, especially the principle of agreement from both parties to be married. Forced marriages occur because one party or both parties who are about to get married do not approve of the marriage being held. Then it is necessary to study specifically about the factors of forced marriages